Humic acid enhanced pyrene degradation by Mycobacterium sp. NJS-1. (February 2022) - Li, Xiaoning; Liu, Hailong; Yang, Weiben; Sheng, Hongjie; Wang, Fang; Harindintwali, Jean Damascene; Herath, H.M.S.K.; Zhang, Yinping
Abstract: The search for nature-based tools to enhance bioremediation is essential for the sustainable restoration of contaminated ecosystems. Humic acid (HA) is an important component of organic matter in soil and water, but its effect on the microbial degradation of organic pollutants remains unclear. In this study, the biodegradation of pyrene by Mycobacterium sp. NJS-1 with and without HA was investigated. Only around 10.5% of pyrene was biodegraded in the pyrene treatment alone, whereas the addition of HA significantly enhanced biodegradation to the point where over 90% of pyrene was biodegraded. The production of 4, 5-dihydropyrene-4, 5-diol and phenanthrene-3, 4-diol indicated the metabolic pathway via attacking of 4, 5-positions of pyrene. Interestingly, 1, 2-dimethoxypyrene was detected with the addition of HA, suggesting that HA induced a new ring-opening pathway involving the attack on the 1, 2-positions of pyrene. The addition of HA first induced protein self-cleavage behavior with a significant increase in phenylalanine, tyrosine, and tryptophan containing large numbers of COO − groups. Furthermore, it altered the intracellular and extracellular ultrastructure of bacterial cells, promoting their growth in size and number as well as reducing the space between them. Overall, HA increased the ring-opening positions of pyrene and facilitated its interaction with bacterial cells, thus improving its biodegradability. Building upon the findings of this study to further research is conducive to the sustainable solution of environmental pollution. Graphical abstract: Image 1 Highlights: The presence of HA promoted pyrene degradation by Mycobacterium sp. NJS-1. Phenanthrene-3, 4-diol and 1, 2-dimethoxypyrene were detected. HA induced distinct morphologies in bacteria cells. Band shifting indicated the complexation of bacterial cells with HA.